দিনলিপি ও আমার শিল্পী জীবনের কথা - আহমদ,আব্বাসউদ্দীন, 1901-1959.; আব্বাসী, মুস্তাফা জামান. (ঢাকা : প্রথমা প্রকাশন, 2009)
Diary and autobiography of Abbasuddin Ahamad, folk singer from Bangladesh.
Includes Index.
00023458
In Bengali.
Keywords: Ahamad, Abbasuddin, -- 1901-1959.; Folk singers -- Bangladesh -- Biography; Lyricists -- Bangladesh -- Biography